Między tekstem a kulturą : z zagadnień przekładoznawstwa - Knapik, Aleksandra R.; Chruszczewski, Piotr P., 1973- (Beyond language, 2018)
"Między tekstem a kulturą: Z zagadnień przekładoznawstwa" [Between the text and culture: on translation studies] is the first volume in the new series Beyond Language, published under the auspices of College for Interdisciplinary Studies, University of Wrocław. This voluminous collection opens the door to translation theory in the Polish perspective, its practice and applications in history and modern times, inviting discussion from the most eminent Polish scholars across the disciplines. Arranged in four major parts (1. Translation theory in historical perspective; 2. Religion in translation - historical and modern perspectives; 3. From theory to practice; 4. Applications, cf. Table of Contents), the material will be of interest to both academics researching translation as a discipline and translators practicing the craft.